PERANAN DINAS KESEHATAN DAERAH PROVINSI SULAWESI UTARA DALAM SISTEM RUJUKAN PASIEN COVID-19 - Harto Necsen Linelejan; Dety Mulyanti (Universitas Katolik Widya Karya Malang, 2023)
Effective COVID-19 patient referral system is crucial to ensure that patients in need of care can receive timely and appropriate treatment. The Regional Health Department of North Sulawesi Province plays a crucial role in the COVID-19 patient referral system in the region. The purpose of this study is to evaluate the role of the Regional Health Department of North Sulawesi Province in the COVID-19 patient referral system. This study was conducted using literature review. The results of the study showed that the Regional Health Department of North Sulawesi Province plays a very important role in coordinating between units within the department, overseeing the implementation of programs and policies, and ensuring the availability of sufficient facilities and medical personnel in the COVID-19 patient referral system. This role has ensured that the COVID-19 patient referral system in North Sulawesi Province runs well and effectively. However, further research can be conducted to deepen the understanding of the COVID-19 patient referral system in the region. Further research can be conducted to compare the COVID-19 patient referral system in other regions in Indonesia, so that a more comprehensive understanding of the role of regional health departments in handling the COVID-19 pandemic in Indonesia can be obtained.